Empresarial para la formalización y desarrollo de los comerciantes informales del cantón Mocache, 2023. - Cabrera Vera, Orlanda Manuela (2025)
This research analyzes business management as a key tool for the formalization and development of informal traders in the canton of Mocache, considering its impact on local economic growth. Initially, the main informal enterprises in the area were identified, highlighting their relevance in the commercial dynamics. Subsequently, the obstacles faced by these traders in their formalization process were examined, emphasizing factors such as limited access to financing, lack of knowledge of regulations, and bureaucratic difficulties. Additionally, the current policies and municipal ordinances promoted by the GAD Municipal were analyzed, assessing their effectiveness in the regularization process of informal traders. The methodology used followed a mixed approach, incorporating data collection techniques such as surveys and interviews with traders and local authorities. Among the main findings, the study identified the need for comprehensive strategies that include business training, tax incentives, and access to microcredits to facilitate the transition to formalization. It is recommended to strengthen cooperation between traders and the GAD Municipal, as well as to develop awareness and technical advisory programs that promote a sustainable and inclusive commercial ecosystem. This study contributes to the design of strategies that foster economic development and job stability in the informal sector.